Response of stomatal conductance, transpiration, and photosynthesis to light and CO2 for rice leaves with different appearance days - Lv, Yuping; Gu, Linhui; Man, Runze; Liu, Xiaoyin; Xu, Junzeng (Frontiers in Plant Science, 2024)
To investigate the dynamics of stomata, transpiration, and photosynthesis under varying light intensities and CO2 conditions during leaf development, the light response and CO2 response of stomatal conductance (gsw), transpiration rate (Tr), and net photosynthetic rate (Pn) were observed for rice leaves at different days after leaf emergence (DAE). The results showed that (1) as photosynthetically active radiation (PAR) increased, leaf gsw, Tr, and Pn initially increased rapidly and linearly, followed by a more gradual rise to maximum values, and then either stabilized or showed a declining trend. The maximum gsw, Tr, and Pn were smaller and occurred earlier for old leaves than for young leaves. The gsw, Tr, and Pn all exhibited a linear decreasing trend with increasing DAE, and the rate of decrease slowed down with the reduction in PAR; (2) as the CO2 concentration (Ca) increased, gsw and Tr decreased gradually to a stable minimum value, while Pn increased linearly and slowly up to the maximum and then kept stable or decreased. The gsw, Tr, and Pn values initially kept high and then decreased with the increase of DAE. These results contribute to understanding the dynamics in gsw, Tr, and Pn during rice leaf growth and their response to varied light and CO2 concentration conditions and provide mechanistic support to estimate dynamic evapotranspiration and net ecosystem productivity at field-scale and a larger scale in paddy field ecosystems through the upscaling of leaf-level stomatal conductance, transpiration, and photosynthesis.